Two Optimal Value Functions in Parametric Conic Linear Programming - Luan, Nguyen Ngoc; Kim, Do Sang; Yen, Nguyen Dong (Journal of optimization theory and applications, 2022)
We consider the conic linear program given by a closed convex cone in an Euclidean space and a matrix, where vector on the right-hand side of the inequality constraint and the vector defining the objective function are subject to change. Using the strict feasibility condition, we prove the locally Lipschitz continuity and obtain some differentiability properties of the optimal value function of the problem under right-hand-side perturbations. For the optimal value function under linear perturbations of the objective function, similar differentiability properties are obtained under the assumption saying that both primal problem and dual problem are strictly feasible.